2002
DOI: 10.1136/bjo.86.11.1265
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic fractionated irradiation of optic nerve sheath meningioma: a new treatment alternative

Abstract: Background: Primary optic nerve sheath meningioma (ONSM) is a rare but almost invariably blinding tumour when its natural history is observed in a "wait and see" strategy. Surgery has hitherto only been advocated in case of progressive disease involving intracranial structures, as it leads to iatrogenic blindness in the overwhelming majority of cases. Therefore, treatment options bearing lesser risk of functional deterioration are highly desirable, both in cases of intracranial involvement as well as during ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
6

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 21 publications
2
59
0
6
Order By: Relevance
“…32,33 To date, the only long-term data reflect the results after treatment using conventional fractionated radiation therapy; 34 however, there is increasing evidence that stereotactic or conformal fractionated radiation therapy may result in improved visual outcome with fewer complications. 29,[35][36][37] I recommend that patients with optic nerve sheath meningiomas who have good visual function be followed without intervention until or unless they begin to experience progressive loss of vision, at which time I recommend stereotactic or conformal fractionated radiation therapy, whereas patients who present with significant visual loss should be given the option to undergo radiation therapy immediately. In such patients, the progression of visual loss may be extremely slow, occurring over many years.…”
Section: Optic Nerve Sheath Meningiomamentioning
confidence: 99%
“…32,33 To date, the only long-term data reflect the results after treatment using conventional fractionated radiation therapy; 34 however, there is increasing evidence that stereotactic or conformal fractionated radiation therapy may result in improved visual outcome with fewer complications. 29,[35][36][37] I recommend that patients with optic nerve sheath meningiomas who have good visual function be followed without intervention until or unless they begin to experience progressive loss of vision, at which time I recommend stereotactic or conformal fractionated radiation therapy, whereas patients who present with significant visual loss should be given the option to undergo radiation therapy immediately. In such patients, the progression of visual loss may be extremely slow, occurring over many years.…”
Section: Optic Nerve Sheath Meningiomamentioning
confidence: 99%
“…Other side effects were dry eye, orbital pain (in a patient suffering form migraine), and iritis, which responded well to local steroid therapy. In contrast, the other studies dealing with pONSM providing clearly documented treatment parameters [57][58][59] showed excellent treatment outcome (improved or stable vision in 100% of patients in both studies) and no toxicity to optic pathways were observed. The follow-up in these studies ranged from 1-7 years (mean, 3 years; median, 2 years), 58 and 1-6 years (median, 35.5 months).…”
Section: Treatmentmentioning
confidence: 47%
“…The characteristics of these studies and the outcome are given in Table 1, including the most recent multi-institutional study by Baumert et al, 78 and smaller studies of Richards et al, 79 Landert et al, 80 a report of a case by Paridaens et al, 81 and the most recent report by Sitathanee et al, 82 all published later on. Liu et al, 58 Becker et al, 59 as well as Pitz et al 57 and Baumert et al 78 reported on pONSM exclusively/separately. Turbin et al 43 provided the longest follow-up, reporting on 18 pONSM of a total of 64 ONSM patients, without specifying the details on the outcome for pONSM.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations